Mendaur ulang sampah kantong plastik Low Density Polyethylene menjadi produk fungsional - Devanny Gumulya; Febriyanti Febriyanti; Fenny Meilani (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2020)
Currently we are accustomed to disposable packaging, the habit generates a lot of waste because we are used to buying, use and dispose of when the lifespan has been exhausted with a consumption pattern like this, Indonesia has now become the world's second-largest plastic waste-producing country. With the product design approach, the student of Universitas Pelita Harapan (UPH) was tasked to recycle plastic waste in UPH environment into a functional product. Based on the results of observation and interviews, one of the waste plastic accumulated in UPH environment is the plastic shopping bag. LDPE is a thermoplastic. A type of plastic that can be formed repeatedly trough heat. The process starts by collecting, sorting, washing, then began the recycling process by heating it with oven and put them unto the mold.  The purpose is to create new material that has an aesthetic quality and good structure. After the waste is processed into a functional product, the results are socialized to students from other majors in a workshop, where each participant must bring their own plastic waste materials. The result of this research and community service is a reduction in  shopping bags waste that exists in UPH environment by 1%, increases millennials' awareness about plastic waste in UPH, and change their perception that garbage plastic bag shopping is not rubbish that should be discarded, but a material that is ready to be recycle and made into a functional product.